Therapeutic Alliance and Rapport Modulate Responses to Psilocybin Assisted Therapy for Depression - Murphy, Roberta; Kettner, Hannes; Zeifman, Rick; Giribaldi, Bruna; Kartner, Laura; Martell, Jonny; Read, Tim; Murphy-Beiner, Ashleigh; Baker-Jones, Michelle; Nutt, David; Erritzoe, David; Watts, Rosalind; et al. (Frontiers in Pharmacology, 2022)
Background: Across psychotherapeutic frameworks, the strength of the therapeutic alliance has been found to correlate with treatment outcomes; however, its role has never been formally assessed in a trial of psychedelic-assisted therapy. We aimed to investigate the relationships between therapeutic alliance and rapport, the quality of the acute psychedelic experience and treatment outcomes. Methods: This 2-arm double-blind randomized controlled trial compared escitalopram with psychedelic-assisted therapy for moderate-severe depressive disorder (N=59). This analysis focused on the psilocybin condition (n=30), who received two oral doses of 25 mg psilocybin, three-weeks apart, with psychological preparation, in-session support, and integration therapy. A new psychedelic therapy model, called ‘Accept-Connect-Embody’ (ACE), was developed in this trial. The primary outcome was depression severity six weeks post treatment (Quick Inventory of Depressive Symptomatology, QIDS-SR-16). Path analyses tested the hypothesis that therapeutic alliance (Scale To Assess the Therapeutic Relationship Patient Version, STAR-P) would predict depression outcomes via its influence on the acute psychedelic experience, specifically emotional-breakthrough (EBI) and mystical-type experiences (MEQ). Results: The strength of therapeutic alliance predicted pre-session rapport, greater emotional-breakthrough and mystical-type experience (maximum EBI and MEQ scores across the two psilocybin sessions) and final QIDS scores (β = -0.22, R2 = 0.42 for EBIMax; β = -0.19, R2 = 0.32 for MEQMax). Exploratory path models revealed that final depression outcomes were more strongly affected by emotional breakthrough during the first, and mystical experience during the second session. Emotional breakthrough, but not mystical experience, during the first session had a positive effect on therapeutic alliance ahead of the second session (β = 0.79, p < .0001). Therapeutic alliance ahead of the second session had a direct impact on final depression scores, not mediated by the acute experience, with a weaker alliance ahead of the second psilocybin session predicting higher absolute depression scores at endpoint (β = -0.49, p < .001). Discussion: Future research could consider therapist training and characteristics; specific participant factors, e.g., attachment style or interpersonal trauma, which may underlie the quality of the therapeutic relationship, the psychedelic experience and clinical outcomes; and consider how therapeutic approaches might adapt in cases of weaker therapeutic alliance.